Audit Energi Menggunakan Intensitas Konsumsi Energi untuk Konservasi Energi di Gedung Kampus - Faniama, Virara; Hanadi; Christian, Hadi; Tomoyahu, Syafril; Pradipta, Justin; Nashirul Haq, Irsyad; Leksono, Edi (Jurnal Otomasi Kontrol dan Instrumentasi, 2024)
Energy auditing is an essential step in optimizing energy use in commercial buildings. This research explores the application of energy auditing with the Energy Consumption Intensity method to improve energy efficiency in campus buildings. Considering the changes in occupancy and activity patterns in the university environment can provide a comprehensive insight into the associated energy consumption patterns. The audit analyzed the building's energy consumption and identified potential energy savings to improve energy efficiency. Energy data was collected and analyzed to evaluate the building's energy performance. Recommended energy conservation measures include updating the lighting system, optimizing the cooling system, and improving the efficiency of equipment use. This research recommends that campus building managers adopt sustainable practices in energy management, which can lead to reduced operational costs and lower environmental impacts. Thus, the energy audit approach with the IKE method is a relevant and effective strategy for achieving energy conservation goals in the university environment. Based on the analysis, the latest IKE for Labtek V is 38.01 (2021), while the IKE for Labtek VI is 16.75 (2021), showing inefficiency of energy use in both buildings inefficient.